Sintesis Pemikiran Al-Ghazali dan Syed Muhammad Naquib Al-Attas sebagai Landasan Manajemen Pendidikan Islam yang Bernilai dan Implementatif - Edo Ferdian; M. Nor Fahmi Fahad; Laili Dewi Amalia; Azima Wahidatu Wildana; Yuliana Nurul Islami (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
Islamic education management in the contemporary era is no longer adequate if understood solely as an administrative activity, but must be built on a solid philosophical, ethical, and spiritual foundation. This article aims to analyze the concept of Islamic education management from the perspective of Al-Ghazali and Syed Muhammad Naquib al-Attas and examine the relevance of its implementation for contemporary Islamic education management. This study uses a qualitative approach with a library research type. Data were obtained from the primary works of both figures and various relevant secondary sources, then analyzed through a comparative-conceptual approach with qualitative content analysis techniques and hermeneutic reading. The results show that Al-Ghazali emphasizes the ethical-spiritual dimension of education through the integration of knowledge, charity, morals, and purification of the soul, while al-Attas emphasizes the epistemological-philosophical dimension through the concepts of ta'dib, adab, and the Islamic worldview. Both have a common ground in the view that Islamic education must be directed at the formation of knowledgeable, civilized, and moral human beings, and should not be reduced to a technical process with neutral value. In terms of implementation, this study synthesizes the thoughts of both figures relevant to strengthening education, leadership, curriculum and learning management, institutional culture formation, and holistic educational evaluation. Therefore, Islamic educational management is ideally built on a foundation of ethical-spiritual and epistemological-philosophical integration to ensure effective, valuable, and transcendental-oriented educational governance.